The relationship between leadership styles and ınnovative work behavior - Güleç, Burcu (My University, 2022)
In today's rapidly changing and globalizing world, it has become very crucial for institutions to survive and maintain their competitive advantage. Organizaitons that have similar assets in many ways can exist in their sectors via innovations. Without a shadow of doubt, the human factor becomes very important in organizaitons in order to create this innovation. In this context, both the leader who will lead the innovation and the people who will ensure the realization of this innovation become the most critical elements in the process. At that point, the qualities that a leader owns have a tremendous effect on the organizational innovation because those qualities have an influence on the innovative working behaviors of the employees, who are the most important part of this innovation. The purpose for which this research has been carried out is to measure the effect that leadership types have on innovative work behaviors of the employees. The sample of the research is employees of a bank serving in Turkey. The findings revealed that the leadership behaviors of the leader affects the employees’ innovation tendency. As hypothesis tests show that transformational and transactional leadership types have a meaningful impact on innovative work behavior of the employees, while laissez-faire leadership type has no effect on innovative work behavior of the employees.

Hızla değişen ve globalleşen günümüz dünyasında, kurumlar için ayakta kalabilmek ve rekabet üstünlüğünü koruyabilmek çok önemli hale gelmiştir. Bir çok yönden benzer varlıklara sahip olan kurumlar, yenilik yaratarak sektörlerinde var olabilmektedirler. Hiç şüphesiz, bu yeniliği yaratabilmek için kurumlarda insan faktörü önemli hale gelmektedir. Bu bağlamda, hem yeniliğe öncülük edecek lider hem de bu yeniliğin gerçekleşmesini sağlayacak kişiler en kritik elementler haline gelmektedir. Tam da bu noktada liderlerin özellikleri, kurumsal inovasyonu etkilemekte çünkü liderlerin özellikleri bu inovasyonun en önemli parçası olan çalışanların yenilikçi çalışma davranışlarını etkilemektedir. Bu araştırmanın amacı, liderlik tiplerinin çalışanın yenilikçi iş davranışı üzerindeki etkisini ölçmektir. Araştırmanın örneklemi Türkiye’de hizmet veren bir bankanın çalışanlarıdır. Bulgular liderin sahip olduğu liderlik davranışlarının, çalışanların inovasyon eğilimi üzerinde etkisi olduğunu ortaya koymuştur. Hipotez testleri, dönüşümcü ve etkileşimsel liderlik tiplerinin çalışanların inovasyon eğilimi üzerinde anlamlı bir etki olduğunu gösterirken, serbest bırakıcı liderlik tipinin ise inovasyon eğilimi üzerinde anlamlı bir etkisinin olmadığını göstermektedir.
Keywords: Business; Innovation Yenilikçi İş Davranısı; Innovative Work Behavior; İnovasyon; İşletme; Leadership; Liderlik; Management; Yönetim